PRESERVATION OF ENRICHING COMPONENTS DURING PRODUCTION AND STORAGE OF CHOUX GINGERBREAD MODEL SAMPLES - Naumova N.L. (Техника и технология пищевых производств)
One of the drawbacks of flour confectionery products is their low physiological value, almost complete absence of vitamins, macro-and microelements. Creating confectionery fortified with essential micronutrients is one of the most urgent tasks of technologist-engineers. The aim of research was to study the preservation of enriching components, namely selenium and a number of vitamins, in the production and storage of gingerbread model samples. As an object of preservation «Yarmarochnye» gingerbreads were used, the production of which was carried out at the «First bakery» (Chelyabinsk city). To enrich the gingerbread the selenium supplement «Celexa» manufactured by «Medbiopharm» (Obninsk city, Kaluga region) was used, for vitamin enrichment - the 991/9 vitamin premix producted by «DSM Nutritional Products Europe Ltd» (Switzerland). Standards addition of enriching additives to the gingerbread formulation was calculated per 100 kcal of products. The studies established relatively high preservation of selenium and B vitamins in the dough kneading and gingerbread molding, with the exception of riboflavin and cyanocobalamin losses. Main vitamin destruction takes place when baking the cakes, which significantly reduces the preservation of pantothenic acid (to 39.5%) of thiamine (to 50.0%), of folic acid (to 60.0%) of cyanocobalamin (to 68.0%) and selenium up to 65.3%; the niacin content being almost unchanged. In 45 days of storage enriched samples greater loss (21.6%) was typical of vitamin E, the loss of other micronutrients was less than 10.0%.